Relationship Between Child Perfectionism and Psychological Disorders - Lozano, Luis Manuel; Valor-Segura, Inmaculada; García-Cueto, Eduardo; Pedrosa, Ignacio; Llanos, Alexia; Lozano, Luis (Frontiers in Psychology, 2019)
Objective: Perfectionism is one of the variables related to the correct emotional development or with the appearance of clinical symptomatology in childhood. A study has been designed to evaluate the differential effect that each dimension of perfectionism (external pressure, self-exigency, and negative self-evaluation) has in a Spanish children sample of general population for each of the following clinical aspects: irritability, worthlessness feelings, thinking problems, and psychophysiological symptoms. Method: By a random cluster sampling, a total of 2,636 children from 8 to 12 years (M = 9.9, SD = 1.2; 51.3% boys) took part in this research. A serial multiple mediators model was used to check the relation between external pressure over the clinical symptoms through self-exigency and negative-self-evaluation. Results: The results have shown a predictive effect of external pressure over a great variety of clinical symptomatology (irritability, worthlessness, thinking problems, and psychophysiological symptoms), a relation mediated by self-exigency and negative self-evaluation. These relations suggest that external pressure and negative self-evaluation are maladaptive dimensions as they predict the appearance of symptomatology, being the level of self-exigency a protective dimension and favoring the child’s positive development. Conclusions: In consequence, these results point to the importance of the study of these variables that can generate difficulties in childhood in order to improve children’s quality of life and their correct development.